Emergence of a new turfgrass insect pest on golf courses in Quebec, the European crane fly [Diptera: Tipulidae] - Simard, Louis; Brodeur, Jacques; Gelhaus, Jon; Taschereau, Élisabeth; Dionne, Julie (Phytoprotection)

(untitled) (Société de protection des plantes du Québec, 2006)
AbstractA survey of European crane fly occurrence was performed in 2002 on 18 golf courses from different climatic regions of Quebec, Canada. At each golf course, the scouting was done weekly from early May to mid-October on three greens and three fairways using a grid and a golf course hole cutter, respectively. The European crane fly (Tipula paludosa), a major turfgrass insect pest, was identified on two golf courses in the Quebec City area. This is the first record of this species in Quebec. These European crane fly larvae were observed from mid-May to the end of August, and adults were detected from late August to mid-September. The European crane fly was found to be a pest on the two golf courses and insecticide applications were used to control the large populations of this insect.